MiR-27a-3p Promotes Non-Small Cell Lung Cancer Through SLC7A11-Mediated-Ferroptosis - Lu, Xuan; Kang, Ningning; Ling, Xinxin; Pan, Ming; Du, Wenjing; Gao, Shan (Frontiers in Oncology, 2021)
Background: Ferroptosis is a newly generated regulatory cell death promoted by the accumulated lipid-based reactive oxygen species (ROS). Solute carrier family 7 member 11 (SLC7A11), the cystine/glutamate antiporter, is known as ferroptosis executor that exhibits a positive correlation with carcinoma progression because of antioxidant function. Nonetheless, it is yet unclear on the understanding of ferroptosis regulation in lung cancer. Methods: Database, qRT-PCR, Western-blot (WB) and immunohistochemistry were utilized to determine SLC7A11 expression and function, as well as genes iron related to necrosis in clinical tissue specimens and cells; Using ferroptosis inducer, inhibitors and SLC7A11 lentivirus to confirm SLC7A11's biological activity in cell viability, oxidative stress, lipid peroxidation and iron ion enrichment in non-small cell lung cancer (NSCLC) in different cells; Using lentivirus to infect lung adenocarcinoma cell lines to acquire miR-27a-3p overexpression and knockdown cell lines, and to detect SLC7A11 level through qRT-PCR and WB; Detecting the influence of up-regulated/down-regulated miR-27a-3p on ferroptosis and other related biological characteristics of lung adenocarcinoma cell lines. Results: Up-regulated SLC7A11 was shown in NSCLC patients and cells and increased SLC7A11 had a relation to the poorly prognostic status of NSCLC patients. Besides, a novel miRNA, miR-27a-3p, was an essential modulator of ferroptosis via directly targeting SLC7A11 in NSCLC cells. Overexpressing miR-27a-3p led to SLC7A11 suppression via directly binding to its 3'-UTR, followed by the reduction of erastin-caused ferroptosis. In contrast, inhibited miR-27a-3p resulted in an increase in NSCLC cells' sensitivity to erastin. Of importance, the accumulated lipid ROS and cell death of iron-peptide mediated by anti-miR-27a-3p can be eliminated by impeding glutamylation process. Our literature collectively uncovered that miR-27a-3p modulated ferroptosis by targeting SLC7A11 in NSCLC cells, illustrating the important role of miRNA in ferroptosis. Conclusion: MiR-27a-3p modulates ferroptosis via targeting SLC7A11 in NSCLC cells, implying the significant role of miR-27a-3p/ SLC7A11 in ferroptosis.